A novel and alternative in vitro method using microwave to study the epithelial-stromal interactions - Sacca, Paula Alejandra (2009)
The goal of the present work was to obtain a simple and reproducible experimental model that would maintain the characteristics of the extracellular physiological environment of breast epithelial cells, both in factors as well as stromal structure, on which we could grow and evaluate changes of normal and tumor breast cells. 3T3-L1 pre-adipocytes (breast stromal cell model) were cultured and irradiated in a microwave oven at different times and potencies. In order to lose their proliferation ability, cells had to be irradiated twice at 650 Watts with a two-minute pulse each. The characteristics of the treated stromal support were analyzed for cell morphology, presence of DNA and proteins. We then evaluated on this support the effect on proliferation and migration of both normal and tumor - murine and human - breast epithelial cells. Both cell types increased their proliferation, while only tumor cells increased migration, thus improving their metastatic capacity. We believe this is a new and simple experimental method of studying epithelial-stromal cell interaction.